Lucillio, Epigrammi - Lucillius, active 1st century; Floridi, Lucia (Texte und Kommentare., 2014)
This is the first modern commentary devoted exclusively to the epigrams of Lucillius, a prolific Neronian poet who, in spite of being one of the most significant representatives of the Greek satirical epigram, has primarily been studied not for his own value, but for the influence he had on Martial. The volume contains an extensive introduction, a new critical text and translation, and a full literary and philological commentary.